Social Impact Analysis of BAZNAS’s Smart Nunukan program in Nunukan Regency Using the SROI method - Sari, Hesti Purnama; Hermawan, Aries; Putri, Diana (Jurnal Ekonomi dan Perbankan Syariah, 2023)
The aim of this research is to determine the social impacts received by Stakeholders from the Nunukan scholarship program for underprivileged recipients in the Baznas district of Nunukan, and to determine the value of these social impacts compared to the amount of investment made by the Baznas district of Nunukan, calculated using the SROI ratio. The sample for this study are recipients of the Nunukan Smart scholarship program in the Baznas district of Nunukan. Data was collected through interviews and questionnaires. The research methodology used is a quasi-qualitative method, which is a design of post positivism. The result of this research is an SROI ratio of 21:1, which means that for every Rp. 1 invested in the Baznas district of Nunukan in its Nunukan Smart program, Rp. 21 of social impact will be created.